Economical synthesis of highly efficient and tunable carbon aerogels for enhanced storage of CO2 emitted from energy sources. (23rd December 2020) - Bhatnagar, Ashish; Pandey, Anant Prakash; Hudson, M. Sterlin Leo; Soni, Pawan K.; Verma, Satish K.; Shukla, Vivek; Sekkar, V.; Tripathi, Manoj; Srivastava, O.N.
Summary: The present investigation reports the synthesis of Carbon Aerogel (CA) with varying pore size and surface area by changing the initial precursor that is, Resorcinol (R) and novel Catalyst (triethyl amine [TEA]) (C) ratio (R/C). The catalyst, TEA allows the gel to dry with negligible shrinkage. The R/C ratio has been kept 1000, 2000 and 3000. The CA with R/C = 1000 has the lowest pore size 1.93 nm, the highest surface area (369.14 m 2 /g) and the highest CO2 uptake of 24.40 wt.% (5.54 mmol/) at 40 atm CO2 pressure. The activated version of optimum CA (R/C = 1000) has been found to have an average pore diameter 1.91 nm and CO2 uptake capacity of 29.56 wt% (6.71 mmol/g) at 25°C which is one of the highest CO2 storage capacity of CAs reported so far. Thus, the present manuscript put forward highly efficient and tunable CAs for enhanced CO2 storage. Abstract : CO2 storage by carbon aerogel.